Different tools to trace geographic origin and seasonality of croaker (Micropogonias furnieri) - Chaguri, Milena P. [UNESP]; Maulvault, Ana Luisa; Nunes, Maria Leonor; Santiago, Debora Aparecida [UNESP]; Denadai, Juliana Celia [UNESP]; Fogaca, Fabiola Helena [UNESP]; Sant'Ana, Lea Silvia [UNESP]; Ducatti, Carlos [UNESP]; Bandarra, Narcisa; Carvalho, Maria Luisa; Marques, Antonio (Elsevier B.V., 2015)
The aim of this study was to use proximate chemical composition, macro and trace elements, fatty acid profile and stable isotopes as traceability tools to assess geographic origin and seasonality of croaker (Micropogonicts fumieri). Croaker from Parnaiba contained higher ash in July and lower fat content than croaker from Santos. In contrast, croaker from Santos had statistically higher proportion of 16:1n-9+16:1n-7, 20:1n-11, 20:1n-9, MUFA and n-3/n-6 ratio than croaker from Parnaiba. Concerning seasonality, croaker caught in July had significantly higher amounts of 14:0, 15:0, 16:1n-9+16:1n-7 and saturated fatty acids than fish caught in December. Concerning elements, significant differences were also detected between seasons for Cl, Ca, Fe, Sr and S, whereas differences between geographic origins were only observed with K. delta C-13 and delta N-15 were statistically different between geographic origins, whereas differences between seasons were only detected in delta N-15 ratio of croaker from Santos. Fatty acids, minerals and stable isotope are effective methods to trace geographic origin and seasonality of croaker. Nonetheless, further investigation is still required with larger samples of croaker to enable the implementation of fatty acids, elements or stable isotope as authenticity tools by food control agencies. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Micropogonias furnieri; Isotope stable; Traceability; Fatty acids; Minerals